Protecting Free and Open Source Software: Solutions in the Digital Millennium Copyright Act - Franco, Katherine A. (Science and Technology Law Review, 2011)
Since the development of the General Public License, Free and Open Source Software (FOSS) developers have used copyright law to protect their software even while the goals of legally protecting FOSS often run contradictory to the policies behind the Copyright Act. Fundamental to FOSS licenses is the requirement that source code remains accessible, under the notion that this openness promotes greater progress in FOSS development and results in more robust software. However, because of the prevalent distribution of source code, FOSS is particularly vulnerable to copyright infringement. FOSS developers have preemptively protected their works by inventively licensing their work to the public. However, enforcing FOSS licenses through traditional litigation under the Copyright Act has proven challenging. The Digital Millennium Copyright Act provides legal protection that arises along with the exclusive rights traditionally provided to authors, including protection for technological measures that control access, protection for technological measures that protect exclusive rights of a copyright owner, and protection for the integrity of copyright management information (CMI). However, these extra protections are seemingly counterintuitive to the fundamentals of FOSS licenses, which seek to make their copyrighted works more accessible and less restricted. This article focuses on the provisions of the DMCA covering CMI. These provisions have rarely been litigated or otherwise analyzed. However, a review of court decisions regarding the CMI provisions of the DMCA suggest that they may prove to be particularly beneficial in protecting FOSS projects because of the emphasis by FOSS camps in managing FOSS licenses. Just as FOSS camps have traditionally utilized copyright protection that is seemingly in opposition to FOSS goals to created legal safeguards for their works, similar results can, and should, be achieved using the CMI provisions of the DMCA.